Effect of microstructure of nanoparticles and surrounding alcohol groups on energy transfer efficiency. (October 2022) - Zhang, Liang; Jing, Yuyan; Qu, Pingping; Wang, Wenjie; Yao, Xinyue; Tian, Linchao
Highlights: The higher water content, the greater the thermal conductivity of alcohol solutions. Thermal conductivity of alcohol nanofluids is obviously higher than the base fluids. There is a non-escaping adsorption layer on the surface of the Cu nanoparticles. Presence of nanoparticles results in the microstructure change of the system. The solid-like microstructure results in an increase of thermal conductivity. Abstract: The low solar thermal conversion efficiency is an obstacle to the development of a new generation of high-efficiency energy-saving technologies. An important measure to improve the conversion efficiency is to improve the thermal conductivity of the working fluid. Nanofluids have a higher thermal conductivity than conventional fluids, which provides a strategy idea toward solving this problem. In this paper, three kinds of traditional fluids, ethanol, ethylene glycol (EG) and 1, 2-propylene glycol (PG), were used as base solutions, and Cu nanoparticles with different volume fractions were added to form their corresponding nanofluids. The thermal conductivity of the different alcohol solutions and their nanofluid systems were simulated using molecular dynamics and the thermal conductivity enhancement mechanisms of these nanofluids on a micro-level were simulated and analyzed. It was found that the thermal conductivity of the ethanol/EG/PG-water solution was positively correlated with the water content of the system. The addition of Cu nanoparticles improved the thermal conductivity of the three kinds of alcohol nanofluids. The existence of base solution molecular adsorption layer on the surface of nanoparticles was an important factor contributing to the improvement of the thermal conductivity of nanofluids. Through the radial distribution function of the nanofluid system, and the visualization of the molecules in the adsorption layer, it was found that the arrangement of base solution molecules in the adsorption layer was similar to the orderly arrangement of solids. This type of solid-like microstructure rendered better heat transfer performance of the nanofluid than the base solution. Within the scope of this study, the maximum increase in the rate of the thermal conductivity of the ethanol/EG/PG-water solutions was 14.2, 30.6 and 22.6 %, respectively. In the alcohol nanofluid system, the thickness of the adsorption layer on the surface of Cu nanoparticles was ∼0.45 nm, which increased or decreased slightly based on the type of base solution. The above findings provide an important reference for improving solar thermal conversion efficiency.